Zygmunt Michałowski, drugi dyrektor Rozgłośni Polskiej RWE - Borzym, Andrzej (Archiwum Emigracji. Studia – Szkice – Dokumenty, 2017)
ZYGMUNT MICHAŁOWSKI, THE SECOND DIRECTOR OF THE POLISH SECETION OF RADIO FREE EUROPE The article id devoted to Zygmunt Michałowski, who replaced Jan Nowak as director of the Polish Section of Radio Free Europe. Michałowski led the Polish Section in the years 1976–1981, when the “Solidarity” and other opposition movements were gaining political significance in Poland. He was an eminent journalist and prudent tactician, who generally continued Jan Nowak’s political line. Michałowski believed that Radio Free Europe’s primary objective, rather than inspire any specific action, was to offer reliable information to Polish listeners.